Properties of eco-friendly self-compacting concrete containing modified treated palm oil fuel ash - Alsubari, Belal; Shafigh, Payam; Ibrahim, Zainah; Alnahhal, Mohammed Fouad; Jumaat, Mohd Zamin (Elsevier, 2018)
Palm oil fuel ash (POFA) is an agro-waste byproduct disposed as landfills without being recycled. Ground POFA is a suitable supplementary cementitious material that can be utilized in different types of concrete. However, problems associated with the reduction of workability and early-age compressive strength of concrete, as well as limited replacement levels of POFA, have been encountered. Heat treatment of ground POFA (T-POFA) can effectively enhance the performance of POFA and reduce its limitations. However, the energy consumed during such heat treatment is high. Moreover, limited original POFA (approximately 30%) can be used to prepare T-POFA. In this study, a new method was introduced to prepare treated POFA, called modified treated POFA (MT-POFA) with full usage of original POFA. MT-POFA was then used as a cement replacement at 0%, 30%, 50%, and 70% to produce sustainable self-compacting concrete. Test results showed that the fresh properties of all concretes containing MT-POFA were ranged within SCC requirements. The mechanical properties exhibited a reduction in the early ages of MT-POFA concretes; however, with increased curing time, these properties were significantly improved. SCC incorporating MT-POFA exhibited significant resistance against rapid chloride permeability test and elevated temperature, and performed better than the control SCC. In general, MT-POFA exhibited significant potential use as a cement replacement in self-compacting concrete.